Role of Small Enterprises in E-Commerce in theRealm of Development Organizations (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Small Enterprises play a vital role in terms of the generation of revenue, employment generation, reducing regional imbalance, and facilitating exports. Not only from the revenue point of view but also from the viewpoint of regional development, these companies play a very crucial role. India is a developing country, and the growth of these companies is of utmost importance. Despite having such vital importance to a Nation, it has been seen that the development of these companies suffers many challenges. To minimize these, there are various development organizations, rural banks, small finance banks, and other government-supported organizations, actively providing products and services to the small enterprise sector. In addition, the boom in the E-commerce market is also giving ample opportunities for these enterprises to overcome these challenges to a certain extent. This paper tries to critically review the services of development organizations as well as the advantages of e-commerce platforms in the context of Assam state so that small enterprises of the state can overcome challenges and eventually may contribute to the GDP growth of the nation.